2021
DOI: 10.3892/ijmm.2021.5043
|View full text |Cite
|
Sign up to set email alerts
|

SETD7 regulates chondrocyte differentiation and glycolysis via the Hippo signaling pathway and HIF‑1α

Abstract: Chondrocytes are well adapted to hypoxia and produce more functional extracellular matrix in low oxygen environments in vitro . In our previous study, methyltransferase SET domain containing (SETD)7 regulated chondrocyte activity in hypoxic conditions. However, the precise association between SETD7 and chondrocyte differentiation under low oxygen partial pressure remains unclear. The association between SETD7 and chondrocyte differentiation was studied by silencing SETD7 in chondrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
(65 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, Nie et al 38 found that dasatinib promoted the chondrogenic differentiation of mesenchymal stem cells by increasing the phosphorylation level of YAP. In addition to regulating the chondrogenic differentiation of stem cells, YAP has been shown to play a key role in the chondrogenesis of C3H10T1/2 and ATDC5 cells 39–41 . Taken together, YAP plays an essential regulatory role in the process of chondrogenesis in various cell types.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, Nie et al 38 found that dasatinib promoted the chondrogenic differentiation of mesenchymal stem cells by increasing the phosphorylation level of YAP. In addition to regulating the chondrogenic differentiation of stem cells, YAP has been shown to play a key role in the chondrogenesis of C3H10T1/2 and ATDC5 cells 39–41 . Taken together, YAP plays an essential regulatory role in the process of chondrogenesis in various cell types.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, Nie et al 38 and ATDC5 cells. [39][40][41] Taken together, YAP plays an essential regulatory role in the process of chondrogenesis in various cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, HIF-1α has been recognized as a protective factor in maintaining normal chondrocyte function, mainly through promoting chondrocyte metabolism, differentiation, and matrix secretion (39)(40)(41). HIF-1α serves as a pivotal factor for chondrocytes by maintaining anaerobic glycolysis and impeding apoptosis via mitophagy (42,43). HIF-1α is also a positive regulator for the expression of SRY-Box Transcription Factor 9 (SOX9), COL2A1, and ACAN and inhibits the expression of COL1A1, COL1A2, COL10A1, and MMP13 to promote chondrocyte differentiation and matrix synthesis (40,(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SETD7 expression is suppressed under hypoxic conditions ( Liu et al, 2015 ). Others have reported that SETD7 is a negative regulator of HIF-1α and downregulates HIF-1α target genes, such as GLUT1, LDHA, PGK1, EPO, PKM2 and VEGF, which are upregulated after SETD7 inhibition ( Li et al, 2021 ; Xiaoshi et al, 2021 ).…”
Section: Setd7-mediated Substrate Modifications and Their Role In Cancermentioning
confidence: 99%